Моделирование магнитотранзисторов на основе одномерного уравнения непрерывности - Glauberman, M. A.; Yegorov, V. V.; Kanishcheva, N. A. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
The magnetotransistor models which are not based on the resolution of two-dimension continuity equation are examined. It is shown that a contradiction between results of these models and results of exact theory vanishes when the resolution of one-dimension continuity equation is applied correctly.